2004
DOI: 10.1016/j.cub.2004.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Action of Histone Deacetylase Inhibitors in a Protein Aggresome Disease Model

Abstract: Protein inclusions are associated with a number of neurodegenerative diseases including amyotrophic lateral sclerosis (ALS). Whether protein aggregates are toxic or beneficial to cells is not known. In ALS animal models, mutant SOD1 forms aggresome-like structures in motor neurons and astrocytes. To better understand the role of protein aggregation in the progression of disease etiology, we performed a screen for small molecules that disrupt aggresome formation in cultured cells. After screening 20,000 compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 15 publications
8
77
0
Order By: Relevance
“…Consistent with this, we found that aggresome formation in Cd 2+ -treated cells was significantly suppressed by the histone deacetylase inhibitor scriptaid (Corcoran et al, 2004) and by the microtubulin depolarizing agent nocodazole (Johnston et al, 1998) (Fig. 8).…”
Section: Vcp Interacts With Hdac6 Through Its C-terminal Tail (#780-806)supporting
confidence: 82%
“…Consistent with this, we found that aggresome formation in Cd 2+ -treated cells was significantly suppressed by the histone deacetylase inhibitor scriptaid (Corcoran et al, 2004) and by the microtubulin depolarizing agent nocodazole (Johnston et al, 1998) (Fig. 8).…”
Section: Vcp Interacts With Hdac6 Through Its C-terminal Tail (#780-806)supporting
confidence: 82%
“…The HDAC-dependent functions of HDAC6 on aggresome formation cannot, however, be generalized since, in a model for SOD1 mutant aggresome assembly involved in amyotrophic lateral sclerosis, HDAC inhibitors prevented the accumulation of scattered mSOD1 aggregates in aggresomes, but HDAC6 neutralization by tubacin did not inhibit this process. Moreover, trapoxin, an HDAC inhibitor which does not inhibit HDAC6, showed an efficient inhibition of aggresome formation (Corcoran et al, 2004). There are, therefore, yet unknown HDAC-dependent mechanisms involved in the control of aggresome formation.…”
Section: Hdac6: a Therapeutic Target?mentioning
confidence: 99%
“…Hence, recent studies have indicated that HDAC inhibitors might prove useful in treatment of such neurodegenerative disorders as Huntington's Disease (37)(38)(39), spinal muscular atrophy ( 40 ), amyotrophic lateral sclerosis (41)(42)(43), and experimental autoimmune encephalomyelitis ( 44 ). Amelioration of neurodegenerative conditions such as oxidative stress ( 45 ), and preservation of white by guest, on March 31, 2019 www.jlr.org…”
Section: Cell Culturementioning
confidence: 99%